(untitled) (Environment & Health, 2020)
The theoretical review of the state of the mental health in the population of Ukraine and the EU countries is presented in the article. The strategic plans of the Conception of the national target program for the protection of mental health of Ukraine to change the inpatient treatment model to the model of environmental psychiatry are considered. The analysis of the process of deinstitutionalization in Western Europe and Ukraine has been carried out. Analysis of the results of the studies on the emotional burnout syndrome among the employees of psychiatric healthcare institutions and other specialties, the phenomena of stigma, self-stigmatization and ways to overcome stigma is presented. Objective: We carried out a comparative estimation of the modern state of the problem of the organization of psychiatric care for the population of Ukraine and EU countries. Materials and methods: The investigations were conducted on the basis of the study of the scientific sources of the domestic and foreign scientists and the analysis of the Laws of Ukraine, Conceptions of the national programs and resolutions of the EU. We applied a method of theoretical analysis. Relevance of the study and problem statement: The conducted analysis of literary sources demonstrates that the human mental health occupies a leading place in socio-political, financial and economic formation of any state and is one of the prior aspects in all countries of the world. A provision of the accessible qualified medical care for every citizen is a general strategic plan in the development of the public health of the population of Ukraine. It is provided in the Conception of the national target program for the protection of mental health of Ukraine for the period up to 2030. Conclusions: Thus, in order to provide a high qualified medical care to the population of Ukraine, the medical workers of all levels should be able to work with the consequences of psychical traumas, depressions and also with the patients with chronic psychical disorders in the stage of remission not only by medicinal treatment but also by mastering psychological methods which will help to overcome the «prediseases» in the doctors. The changes are provided in the Conception of the national target program to protect the mental health of Ukraine for the period up to 2030, it is impossible without understanding of the real situation, reliable feedback, monitoring, analysis and evaluation.